2001
DOI: 10.1007/s002640100231
|View full text |Cite
|
Sign up to set email alerts
|

Osteoid osteoma: the results of surgical treatment

Abstract: Between 1987 and 1999 we diagnosed and treated 110 patients with osteoid osteoma. Sixty patients were younger than 20 years. One hundred and four patients had characteristic pain at night. The mean duration of symptoms before surgery was 16 months. One hundred and four symptomatic patients were treated operatively with either wide resection or curettage. Ninety-one patients had immediate and complete relief of pain. The average follow-up was 2.5 years.Résumé Entre 1987 et 1999 nous avons traités 110 malades so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 15 publications
3
53
1
7
Order By: Relevance
“…The rate of recurrence with surgical therapy ranges from 0% to 12% in published series [13,58,64,70,71]. Disadvantages of these approaches include activity restrictions if the tumor was in a weightbearing location [70], the need for plating in some patients [13,64], donor site morbidity if grafting is used [71], and postoperative fracture [64].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of recurrence with surgical therapy ranges from 0% to 12% in published series [13,58,64,70,71]. Disadvantages of these approaches include activity restrictions if the tumor was in a weightbearing location [70], the need for plating in some patients [13,64], donor site morbidity if grafting is used [71], and postoperative fracture [64].…”
Section: Discussionmentioning
confidence: 99%
“…Persistence of symptoms greater than 1 month after RFA can be regarded as treatment failure and additional therapy may be considered [8]. With successful surgery, relief of symptoms occurs within 24 hours in 91% and within 48 hours in 9% of patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…Rosenthal et al [32] reported an average hospital stay of 4.7 days for open surgery. Patients also may require a period of protected weightbearing (up to 3 months [44]), and they may experience pain arising from the resected lesion or graft donor sites. They also may need to restrict their normal activities for a prolonged time [18].…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnoses include: osteoblastoma, stress fracture, abscess, intracortical osteosarcoma, enostosis [15]. Surgical excision is the most common treatment; en-bloc resection along with the surrounding reactive bone is associated with a lower rate of recurrence, even though it is associated with higher risk of fracture because of bone loss [16]. Recent studies report an equivalent rate of success to surgery using percutaneous CT-guided techniques such as laser or radio-frequency ablation [17,18].…”
Section: Introductionmentioning
confidence: 99%